Use of Learning CD Media to Improve Student Motivation and Mathematics Learning Outcomes - Budiono Budiono (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2018)
Learning CD Media is a systematically designed media that can attract students. The use of learning CD media can improve the motivation and the learning outcomes of mathematics on determining the various simple wake-up nets for students of SD Negeri 1 Kalijaran. The purpose of this study is to find out how much improvement of motivation and student learning outcomes about determining various simple wake-up nets using learning CD media. Research is a classroom action research consisting of 4 stages (planning, implementation, observation, and reflection) in two cycles. Data collection techniques used are the test techniques, data retrieval tests before and after the action are held using the CD learning media. The method used in this research is classroom action research with data collection technique through observation, interview, and documentation. The results of the research cycle I showed 7 students (53.8%) achieve mastery learning, which has not completed 6 students (46.2%). The average value of students increased from pre-cycle 58.46 to 69.61. Cycle II there are 13 students (100%) achieve learning mastery. The average value of cycle II students increased from cycle I 69.61 to 84.62. Based on the observation, students also experienced an increase in learning motivation in the first cycle of 75.4 percent to 94 percent in cycle II. The conclusion of the study that the use of learning CDs can improve the motivation and learning outcomes of students of grade V SD Negeri 1 Kalijaran second semester Year of Study 2015/2016.